Ziziphus mauritiana Lam. – A Promising Tropical Fruit with Antidiabetic Potential - Sruthi Gopan, M.; Sudha Bai, R. (Indian Forester, 2024)
A comparative evaluation of aqueous and methanolic fruit extracts from Ziziphus mauritiana Lam. raw and preserved samples for antidiabetic activity was carried out using assays on inhibition of alpha amylase and alpha glucosidase activities. The study confirmed that the methanolic fruit extract possess higher percentage of inhibitory activity than the aqueous extract for both the assays. The extracts from raw fruit indicated higher inhibition for alpha amylase than the extract from preserved fruit. The IC50 values for alpha amylase inhibition were in the order 7.98±1.43 (ZMR methanolic) < 9.52±2.78 (ZMR aqueous) < 10.84±1.65 (ZMP methanolic) < 19.98+2.52 (ZMPaqueous) < 35.23+3.09 (standard Acarbose). All extracts were detected as superior to the standard acarbose in inhibiting alpha amylase. In alpha glucosidase inhibition assay, the preserved fruit extracts were detected as superior to raw samples with IC50 values as 33.78±3.24 (Acarbose) < 38.89 ± 2.94 (ZMP methanolic) < 41.08±1.28 (ZMP aqueous) < 81.10±3.66 (ZMR methanolic) < 93.73±3.16 (ZMR aqueous) and the standard acarbose was more potent inhibitor than the ZMP methanolic sample. FTIR profiling of extracts indicated the sharp prominent peaks indicating the presence of different functional groups. Antinutritional analysis to detect the quantity of saponin, tannin, oxalate and phytic acid suggested phytic acid (5.48+0.85 mg/g) as the major antinutritional factor present in the raw fruit extracts and their levels are not exceeding threshold limits.